Full mouth rehabilitation for severely worn dentition using fixed prostheses and tooth-supported partial overdenture: a case report. - Chu, Seng Boon (IIUM Journal of Orofacial and Health Sciences, 2021)
Rehabilitation of severely worn dentition represents a significant clinical challenge, especially when the restorative space is not sufficient. Creating restorations that fulfil the aesthetic, occlusal and functional parameters are essential to long-term success. This case report describes a 48-year-old male, who had severely worn dentition, which resulted in collapsed vertical dimension. The initial treatment involved careful planning, stabilization of existing dental diseases and construction of provisional prostheses at increased vertical dimension. Once the compatibility of the new vertical dimension had been confirmed, permanent reconstruction was performed. As with all full mouth prosthetic rehabilitation cases, equal-intensity centric occlusal contacts on all teeth and an anterior guidance in harmony with functional jaw movements were critically taken into account in each treatment phases.